BOYCOTT MOVEMENTS AND STOCK RETURN VOLATILITY: EVIDENCE FROM INDONESIA’S CONVENTIONAL AND ISLAMIC MARKETS - Rafli Ananta Zikri; Muhammad Nur Faaiz Fathah Achsani; Asep Nurhalim (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2026)
Geopolitical tensions and consumer boycott movements have increasingly become sources of uncertainty in financial markets, yet their implications for stock return volatility remain underexplored, particularly in dual financial systems. This study examines the influence of boycott movements and macroeconomic factors on the volatility of stock returns of Indonesia’s traditional and Islamic stock markets. Daily time series data for the period between January 2021 and April 2025 was considered in order to examine the behaviour of the IDX Composite (IHSG) and Indonesia Sharia Stock Index (ISSI). The volatility dynamics were assessed by applying ARCH/GARCH models, while short-term and long-term relationships were analyzed through the use of the Autoregressive Distributed Lag (ARDL) approach. The results found that the Islamic stocks showed higher resilience compared to traditional shares as indicated by the rapid convergence towards the long-term equilibrium and reduced reactions to shocks associated with the boycott movement. The evidence caused a significant increase in the volatility of the IHSG in the long run; however, it did not impact the volatility of the ISSI because of the protective function of Sharia-based stock selection systems. The reduction of the stock market volatility due to the positive effect of inflation and industrial production rates on stock returns has been found; on the other hand, exchange rate depreciations have opposite effects. Oil prices and sentiment index influence is inconsistent and mostly short-term.